Use of tocilizumab in patients with SARS-CoV-2 at Hospital Nacional Dos de Mayo – Lima, 2020 - Cuba Pérez, Katya (2022)
Objective: To determine the characteristics of the use of tocilizumab (TCZ) in patients hospitalized for SARS-CoV-2, at the Dos de Mayo National Hospital in the months of April to September 2020. Methodology: Descriptive study of transverse cut. The sample consisted of 141 patients infected with SARS-CoV-2, from whom complete information on registered medical prescriptions and medical records was collected. Results: Age was 58.9 ± 11.2 years, 78% were male, weight was 79.6 ± 12.0 Kg, showing that 41.8% and 44.2% were overweight and obese, respectively. In addition, 99.3% of patients showed respiratory rate greater than 22 breaths/minute, 97.2% had blood pressure of less than 100 mmHg and 99.3% had oxygen saturation (SpO2) less than 85% and the common inflammatory markers were PCR>100 mg/dL (75.2%), Ferritin>700 ng/mL (59.6%), D-Dimer> 1000 µg/mL (77.3%), DHL>350 U/L (58.9%) and IL-6>40 pg/mL (48.9%). On the other hand, a total of 275 TCZ units were administered, with a total cost of S/ 703 872,40. The average hospital stay was 17,8 ± 13,6 days, observing that 55.3% died. Conclusion: the main characteristic of the use of TCZ at the Dos de Mayo National Hospital was the prescription of this monoclonal antibody in patients hospitalized with severe COVID-19, a total cost of S/ 703 872,40 and no improvement in survival rates mortality.